Tai Chi and Qigong for cancer-related symptoms and quality of life: A systematic review and meta-analysis - Wayne, P.M. (J Cancer Surviv, 2017)
PURPOSE: Summarize and critically evaluate the effects of Tai Chi and Qigong (TCQ) mind-body exercises on symptoms and quality of life (QOL) in cancer survivors. METHODS: A systematic search in 4 electronic databases targeted randomized and non-randomized clinical studies evaluating TCQ for fatigue, sleep difficulty, depression, pain, and quality of life (QOL) in cancer patients, published through August 2016. Meta-analysis was used to estimate effect sizes (ES, Hedges’ g) and publication bias for randomized controlled trials (RCTs). Methodological bias in RCTs was assessed. RESULTS: Our search identified 22 studies, including 15 RCTs that evaluated 1283 participants in total, 75% women. RCTs evaluated breast (n=7), prostate (n=2), lymphoma (n=1), lung (n=1), or combined (n=4) cancers. RCT comparison groups included active intervention (n=7), usual care (n=5), or both (n=3). Duration of TCQ training ranged from 3 to 12 weeks. Methodological bias was low in 12 studies and high in 3 studies. TCQ was associated with significant improvement in fatigue [ES=−0.53, p<.001], sleep difficulty [ES=−0.49, p=.018], depression [ES=−0.27, p=.001], and overall QOL [ES=0.33, p=.004]; a statistically non-significant trend was observed for pain [ES=−0.38, p=.136]. Random effects models were used for meta-analysis based on Q-test and I-squared criteria. Funnel plots suggest some degree of publication bias. Findings in non-randomized studies largely paralleled meta-analysis results. CONCLUSIONS: Larger and methodologically sound trials with longer follow-up periods and appropriate comparison groups are needed before definitive conclusions can be drawn, and cancer- and symptom-specific recommendations can be made. IMPLICATIONS FOR CANCER SURVIVORS: TCQ shows promise in addressing cancer-related symptoms and QOL in cancer survivors.